Replicating genotype–phenotype associations - Chanock, Stephen J.; Manolio, Teri; Boehnke, Michael; Boerwinkle, Eric; Hunter, David J.; Thomas, Gilles; Hirschhorn, Joel N.; Abecasis, Goncalo; Altshuler, David; Bailey-Wilson, Joan E.; Brooks, Lisa D.; Cardon, Lon R.; et al. (Nature (London), 2007)
What constitutes replication of a genotype–phenotype association, and how best can it be achieved? Gene association pitfalls Reviews of the many genetic association studies published recently give pause for thought: there are many false positives and questionable genotype–phenotype associations in the literature. A working group set up by the National Cancer Institute and National Human Genome Research Institute has been tackling the thorny question of what constitutes replication of a genotype–phenotype association, and the initial results are published this week. Guidelines on best practice for reporting initial and replication studies are presented. But it's clear that a series of studies is sometimes necessary to confirm critical genotype–phenotype associations.